Copper chelator ATN-224 inhibits endothelial function by multiple mechanisms - Lowndes, Sarah A.; Sheldon, Helen V.; Cai, Shijie; Taylor, Jennifer M.; Harris, Adrian L. (Microvascular research, 2009)
Copper is required for the proliferation of endothelial cells and copper-lowering therapy reduces tumour growth in animal models. It has been reported that ATN-224, a novel copper chelator, potently inhibits the activity of the copper-dependent enzyme superoxide dismutase 1 (SOD1) in endothelial cells. We performed microarray analysis of gene expression in endothelial cells exposed to ATN-224 which revealed upregulation of stress response genes including heme-oxygenase 1 (HO-1) and differential regulation of several genes previously implicated in angiogenesis including CXCR4, ANGP2, PGES2, RHAMM, ITB4 and AQP1 ( p < 0.01). These changes were confirmed on qPCR. Treatment of HUVEC with ATN-224 caused increased superoxide levels, phospho-ERK signalling, nuclear NRF1 expression, HO-1 expression and induction of the anti-apoptotic proteins P21, BCL2 and BCLXL. There was also nuclear translocation of SOD1. SOD1 RNA interference replicated the effects of ATN-224 on endothelial cell function but did not cause upregulation of HO-1 or PGES2, suggesting additional mechanisms of action of ATN-224. Downregulation of AQP1, which has been shown to have a role in angiogenesis, was seen with both ATN-224 and SOD1 siRNA. AQP1 expression could be rescued after ATN-224 by added copper. RNA interference to AQP1 inhibited endothelial proliferation and migration, confirming the role of AQP1 in endothelial cell function. Therefore regulation of AQP1 may represent an important action of copper chelation therapy.